SYSTEMATIC LITERATURE REVIEW (SLR): PENYALAHGUNAAN WIFI PUBLIK TERHADAP ORANG AWAM YANG ADA DI INDONESIA - Eddy Ryansyah; Agung Susilo Yuda Irawan (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2023)
The use of the internet on computer network devices in the current technological era certainly very easy for us in daily life to work and other activities in cyberspace. There are so many places to eat or other public places that use computer network devices, namely wifi so that visitors feel at home or feel happy because they have the facilities that are needed by them, namely the internet. However, it is undeniable that there are public wifi devices that have a negative impact because they are free. One solution to prevent internet network users from using negatively charged public wifi can be done by understanding what steps must be taken before and after accessing public wifi. Therefore, the purpose of this study is to provide understanding and learning to ordinary people in Indonesia to minimize or rather eradicate the use of the internet network on public wifi which has a negative impact in public spaces. In realizing the above, the author uses the method of taking 30 journal papers that have been published through Google Scholar with a range of years between 2018 and 2022 to be researched and analyzed using the SLR (Systematic Literature Review) method. SLR is a systematic method used to review a topic in the form of a journal paper to provide opinions on solving problems. Based on this research, it was found that public wifi in computer network learning can improve the problem-solving ability of ordinary users. Based on the literature review conducted, the level of understanding of ordinary people in Indonesia can be developed by learning computer networks on social media and in articles on the internet.